Photoluminescence at room temperature in amorphous SrTiO3 thin films obtained by chemical solution deposition - Pontes, F. M.; Longo, Elson [UNESP]; Leite, E. R.; Lee, EJH; Varela, José Arana [UNESP]; Pizani, P. S.; Campos, CEM; Lanciotti, F.; Mastelaro, V; Pinheiro, C. D. (Elsevier B.V., 2003)
Intense photoluminescence in highly disordered strontium titanate amorphous thin films prepared by the polymeric precursor method was observed at room temperature (300 K). The luminescence spectra of SrTiO3 amorphous thin films at room temperature revealed an intense single-emission band in the visible region. X-ray absorption near edge structure was used to probe the local atomic structure of SrTiO3 amorphous and crystalline thin films. Photoluminescence intensity in the 535 nm range was found to be correlated with the presence of non-bridging oxygen defects. A discussion is presented of the nature of this photoluminescence, which may be related to the disordered structure in SrTiO3 amorphous thin films. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: thin films; amorphous thin films; photoluminescence; SrTiO3